Pengolahan Fitoremediasi Dengan Paku Air (Azolla microphylla) untuk Menurunkan Kadar BOD dan TSS Limbah Cair Rumah Makan - Dewi Septiana Wati; Bambang Suwerda; Narto Narto (Sanitasi: Jurnal Kesehatan Lingkungan, 2011)
Activities at Timbul Roso Restaurant generate not only useful product but also causing negative impacts such as liquid waste which is potential to harm people’s health and pollute the environment if it is not adequately processed. The preliminary survey results on the liquid waste revealed that the BOD and TSS concentration were 538 mg/l and 470.50 mg/l respectively, or had not yet fulfilled the quality standard permitted by the Decree of Minister of Environment No. 112/2003 about Domestic Liquid Waste Quality Standards. This study was aimed to understand whether phytoremediation treatment with water ferns (Azolla microphylla) could reduce BOD and TSS concentration of Timbul Roso Restaurant’s liquid waste by doing an experimental study with pre-post test control group design. Samples was obtained by using time composite method among the different times sequence of the production process to homogenized the waste. Afterwards, sample were treated and examined in the laboratory to record both parameters. The result later analyzed descriptively and statistically by using one tail paired and independent t-test. The results showed that des-criptively, the average BOD concentration decreased from 1724 mg/l to 610,33 mg/l or 64,12 %; and the average TSS concentration decreased from 2018,67 mg/l to 100,33 mg/l or 95,28 %. The corresponding statistic tests showed significant confirmation, i.e. p=0,0075 for BOD and p=0,0055 for TSS. Based on the results, it can be concluded that Phytoremediation treatment with Azolla microphylla is able for reducing BOD and TSS concentration from the liquid waste, however both parameters still have not met the requisite standards.